An evaluation of spoken corpus‐based resources in undergraduate interpreter training. (12th August 2013) - Bale, Richard
<x xml:space="preserve">Abstract</x> The use of corpus‐based materials in language learning and translator training has gained momentum in recent years. Based on the assumption that the exploitation of such resources can be extended to the field of interpreter education, this paper presents the findings from four case studies, in which the BACKBONE corpus was used in the training of undergraduate interpreting students. During each study, students were asked to indicate how they had used the materials and to express their opinions about the resources from a user‐perspective. The paper provides an evaluation of the materials and suggests methods of exploiting spoken corpus‐based resources in the undergraduate interpreting context.